2012
DOI: 10.1590/s0004-28032012000100003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of HFE gene polymorphism on sustained virological response in patients with chronic hepatitis C and elevated serum ferritin

Abstract: -Context -Abnormal serum ferritin levels are found in approximately 20%-30% of the patients with chronic hepatitis C and are associated with a lower response rate to interferon therapy. Objective -To determine if the presence of HFE gene mutations had any effect on the sustained virological response rate to interferon based therapy in chronic hepatitis C patients with elevated serum ferritin. Methods -A total of 44 treatment naïve patients with histologically demonstrated chronic hepatitis C, all infected with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…On the other hand the results of this study are similar to the study of Coelho-Borges et.al that included Brazilian patients with HCV genotypes other than genotype-1 who mentioned the negative effect of H63D mutation on the sustained virological response to IFN & Ribavirin treatment and furthermore they concluded that the finding of HFE polymorphism is a durable predictor of non-response in his study. 31 The results of our study also showed that Carriers of S65C mutations specifically the T allele (HFE 193 A>T) gene polymorphism have 9.2 times risk for not responding to interferon than non-carriers which can be considered a predictor of response to Interferon based therapy. In 2012 Ishizu et.al studied the effect of HFE mutations in Japanese patients with HCV; their study included 251 CHCV patients.…”
Section: Discussionsupporting
confidence: 59%
“…On the other hand the results of this study are similar to the study of Coelho-Borges et.al that included Brazilian patients with HCV genotypes other than genotype-1 who mentioned the negative effect of H63D mutation on the sustained virological response to IFN & Ribavirin treatment and furthermore they concluded that the finding of HFE polymorphism is a durable predictor of non-response in his study. 31 The results of our study also showed that Carriers of S65C mutations specifically the T allele (HFE 193 A>T) gene polymorphism have 9.2 times risk for not responding to interferon than non-carriers which can be considered a predictor of response to Interferon based therapy. In 2012 Ishizu et.al studied the effect of HFE mutations in Japanese patients with HCV; their study included 251 CHCV patients.…”
Section: Discussionsupporting
confidence: 59%
“…Some studies have proposed that ferritin, being an acutephase reactant, behaves as a marker of more active and advanced liver disease. Patients with chronic HCV infection and high serum ferritin levels reportedly have significantly more severe liver inflammation and fibrosis than do patients with normal serum ferritin levels [7,33] . In our study, patients with viral persistence had slightly elevated ferritin levels.…”
Section: Discussionmentioning
confidence: 95%
“…Finally, Gilbert's syndrome is characterized by benign unconjugated hyperbilirubinemia with a frequency of 5.0% to 14.8% in Europe [6] . Most reports on the coexistence of monogenic liver diseases and HCV infection have focused primarily on hereditary hemochromatosis [7] because elevated iron levels are necessary for viral replication [8,9] . Although the associations of HCV infection with alpha-1 antitrypsin deficiency [10,11] and Gilbert's syndrome [12][13][14] have been investigated, the association of HCV infection with Wilson's disease remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, another study reported no correlation between HFE polymorphisms and HCV in Majorcan patients treated with pegylated-interferon plus ribavirin (321). By contrast, heterozygosity for H63D and/or C282Y HFE gene mutation has been shown to be associated with the lack of SVR to pegylated-IFN and ribavirin combination therapy in patients with chronic HCV (322). Taken together, the MHC-Ib protein HLA-H/HFE is strongly expressed by a variety of cells such as Kupffer cells, circulating monocytes/macrophages and intestinal crypt cells.…”
Section: Nef-mediated Downregulation Of Hla-h Expression Contributes mentioning
confidence: 99%